INFLUENCIA DE LA AUTONOMÍA DEL APRENDIZAJE EN LA CALIDAD DE LA FORMACIÓN PROFESIONAL EN LA UNMSM - Ríos Delgado, Teresa (2012)
The basis of the autonomy of the learning begins with the different learning theories – constructivism, cognitive, behaviorist, etc. The concept of the autonomy of the learning can be appreciated from diverse authors and contexts. The autonomous learning is showed up based on the conditions, characteristics, strategies and techniques for its development as well as the faculty’s role. The objective of the present research is to contribute with a model of autonomous learning in the quality of the professional formation of the graduate of San Marcos University. The used method is the ex pos facto, having as participants to the fifth superior of the Faculties of Administrative Sciences, Education, Medicine and Law and Political Science. In Instruments of gathering of data a check off list of survey was designed. As conclusion of this research, the general hypothesis established that the Style of Autonomous Learning contributes to elevate the Quality of the Professional Formation of the students of the last semesters of UNMSM is accepted.